PEMAHAMAN MAHASISWA TERHADAP ETIKA BISNIS SYARIAH DALAM KONTEKS KURIKULUM PROGRAM STUDY BANK SYARIAH - Trisyanti Amanda (Jurnal Al Wadiah, 2023)
This study can provide benefits, especially for students' understanding of Islamic business ethics in various curriculum frameworks of the Islamic Bank Study Program. By using a qualitative approach and using several research methods, among others, interviewing students and analyzing the content of curriculum materials to understand the extent to which the principles of Islamic business ethics are reflected in their perceptions and attitudes. Results show that students' understanding of Islamic business ethics is influenced by various factors, including teaching methods, financial literacy and practical experience. This variability in the level of understanding can give rise to a wide variety of challenges in effectively carrying out the values of Islamic business ethics. In the context of the curriculum, this research can provide valuable input to improve the learning process, especially in this area of Islamic business ethics. Simple applications of this research include, among others, the development of more effective learning strategies and the emphasis on positive experiences that can enhance the understanding and application of Islamic business ethics principles in the real world. Not only can this study contribute to the understanding of how the curriculum can be improved by reflecting the values of Islamic business itself to students, but this study can also provide different and in-depth perspectives on the various challenges and needs of Islamic business ethics.